2023
DOI: 10.1002/rev3.3385
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teachers' day‐to‐day classroom management practices and anxiety in primary school children: A systematic review

Abstract: Anxiety problems are common in children and can have profound adverse effects on personal, social and academic life. Almost 40% of anxiety disorders emerge before age 14, making primary schools invaluable settings for prevention and early support of child anxiety. Research indicates that school-based interventions can be costly and difficult to schedule, school staff lack confidence to deliver them effectively, and outcomes are mixed. One solution may be for school staff to adapt and enhance their day-to-day p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In a poorly managed classroom, both effective teaching and learning processes fail (Jones & Jones, 2012). Research has demonstrated that classroom management plays a crucial role in enhancing the overall quality of education (Akgün, Yarar, & Dinçer, 2011;Korpershoek, Harms, de Boer, van Kuijk, & Doolaard, 2016) and significantly influences student outcomes (see Manley, Tu, Reardon, & Creswell, 2023). A meta-analysis conducted by Korpershoek et al (2016) clearly revealed a positive relationship between classroom management and student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a poorly managed classroom, both effective teaching and learning processes fail (Jones & Jones, 2012). Research has demonstrated that classroom management plays a crucial role in enhancing the overall quality of education (Akgün, Yarar, & Dinçer, 2011;Korpershoek, Harms, de Boer, van Kuijk, & Doolaard, 2016) and significantly influences student outcomes (see Manley, Tu, Reardon, & Creswell, 2023). A meta-analysis conducted by Korpershoek et al (2016) clearly revealed a positive relationship between classroom management and student outcomes.…”
Section: Introductionmentioning
confidence: 99%